Changes in Family Trust and Psychological Intimacy Influenced by Social Media (International Journal of Scientific Trends, 2026)
This article analyzes in detail the influence of social networks on modern family life, in particular, the patterns of change in family trust and psychological closeness. It is highlighted that the expansion of forms of communication in the digital environment, on the one hand, allows strengthening ties between family members, and on the other hand, creates problems related to trust, personal boundaries, and emotional security.